Gas Permeability and Production Potential of Marine Hydrate Deposits in South China Sea - Shen, Pengfei; Li, Gang; Liu, Jiangfeng; Li, Xiaosen; Zhang, Jinming (Energies, 2019)
The permeability of marine sediments is critical to the gas production assessment of hydrate reservoirs. In this work, the sample of natural marine sediments was obtained from Shenhu Area of South China Sea at the depth of 1600 m, and the gas permeability of the sample was measured in the laboratory under various confining pressures. The porosity of the sample decreased from 41.82% to 29.54%, and the effective gas permeability of the sample decreased from 2.638 x 10(-16) m(2) to 0.872 x 10(-16) m(2) as the confining pressure increased from 0 to 23 MPa. The gas permeability of the natural sediments was determined to be 1.535 x 10(-16) m(2) with confining pressure of 15 MPa and porosity of 32%. The deformation of sample in longitudinal direction was sensitive to the confining pressure, and the compressibility in the radial direction was limited. On the basis of the experimental results, the particle size term in the classical Kozeny-Carman equation was revised by correction factor N, and the experimental results fitted well with the curves with N = 2.40. Moreover, the gas production potential at the site of W-17 in the Shenhu Area was numerically studied based on the measured gas permeability. The simulation results showed that the cumulative volume of produced gas was approximately 1.46 x 10(6) ST m(3) after 30 years. A new enlarged permeable well wall method was proposed to improve the poor gas production caused by low permeability. The cumulative gas production increased by 2.7 times as the permeable well wall radius increased from 0 to 5 m. Regarding the gas and water production rates, water production increased with the increase of permeable well wall radius. Spatial distributions of hydrate and gas saturations, pressure, and temperature were investigated as well.